2024
DOI: 10.4103/ijem.ijem_321_23
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Battle Within: Shedding Light on the Co-existence of Sarcopenia and Sarcopenic Obesity among Participants with Type 2 Diabetes in a Tertiary Care Hospital, Gujarat

M Yogesh,
Mansi Mody,
Naresh Makwana
et al.

Abstract: Introduction: Type 2 diabetes (T2DM) is characterised by chronic hyperglycaemia due to abnormal insulin secretion and/or utilisation. Currently, sarcopenia has emerged as a new complication of T2DM, which increases the risk of physical disability, and even death. The study aims to estimate the prevalence of sarcopenia and sarcopenic obesity (SO) as well as their association with various other factors related to T2DM. Methods: The study was an observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…The sarcopenic obesity rate in our diabetic group aligns closely with that reported in a prior Indian study [ 30 ], which reported a 30% prevalence of sarcopenic obesity in diabetic patients. In terms of risk factors, our logistic regression analyses revealed many established associations between sarcopenia and sarcopenic obesity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The sarcopenic obesity rate in our diabetic group aligns closely with that reported in a prior Indian study [ 30 ], which reported a 30% prevalence of sarcopenic obesity in diabetic patients. In terms of risk factors, our logistic regression analyses revealed many established associations between sarcopenia and sarcopenic obesity.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of risk factors, our logistic regression analyses revealed many established associations between sarcopenia and sarcopenic obesity. Age over 65 years had 2- to 3-fold increased odds for both conditions, consistent with well-evidenced risks tied to aging [ 30 32 ], diabetes duration over 10 years, and uncontrolled diabetes (HbA1c over 8%), which were also independently associated with increased odds of sarcopenia and sarcopenic obesity in the present study. Multiple studies corroborate diabetes and poor glycemic control as predictors of accelerated muscle deterioration and functional decline [ 30 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 89%